(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this article, the problems of further improvement of the activities of the bodies of inquiry authorized to conduct an inquiry and inquiry in our country before the start of the investigation are scientifically investigated. Also, prior to the investigation, based on a comparative analysis of the legislation of developed countries, a number of legal acts regulating operational search activities were studied with the aim of further improvement and proposals were made for making changes and additions to the current legislation.